Chapter Fungi from the sediments of the harbour of Livorno as potential bioremediation agents - Florio Furno, Matteo (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The harbour's sediments are among the biotypes most affected by contamination by pollutants due to anthropogenic activities. The porpoise of this work is to perform a preliminary screening on 74 fungi previously isolated in the polluted sediments of the harbour of Livorno, to identify those endowed with oxidative capabilities and to evaluate the potential producers of metabolites or enzymes of interest, for potential applications in future environmental bioremediation. The results have shown that 26 (35.1%) out of 74 tested fungi produced positive oxidation signal on at least one media